The environmental graphics identification in Malaysia's autism school design / Mohammad Shahidan Rosli, Nor Hazirah Hasri and Sarah Rahman - Rosli, Mohammad Shahidan; Hasri, Nor Hazirah; Rahman, Sarah (College of Built Environment, 2023)
Autism is a developmental disorder that has a substantial impact on a person's verbal and verbal communication skills, as well as social interaction.